J-dimer emission in interwoven metal–organic frameworks. Issue 17 (16th April 2020) - Newsome, Wesley J.; Chakraborty, Arnab; Ly, Richard T.; Pour, Gavin S.; Fairchild, David C.; Morris, Amanda J.; Uribe-Romo, Fernando J.
Abstract : J-dimer emission is an emergent property that occurs when pairs of ground-state fluorophores associate within multivariate MOFs producing tunable red shifted emission. Abstract : J-dimer emission is an emergent property that occurs when pairs of ground state fluorophores associate, typically in a dilute solution medium. The resulting fluorescence is shifted with respect to the monomer. J-dimer emission, however, has never been observed in concentrated dispersions or in the solid state. We posited that multivariate (MTV) MOFs with double interwoven structures would help to isolate these dimers within their crystalline matrix. Using this strategy, J-aggregate density was controlled during crystallization by following a substitutional solid solution approach. Here, we identified the presence of J-dimers over the entire composition range for interwoven PIZOF-2 /NNU-28 structures with variable amounts of a diethynyl-anthracene aggregate-forming link. We produced bulk crystals that systematically shifted their fluorescence from green to red with lifetimes (up to 13 ns) and quantum yields (up to 76%) characteristic of π–π stacked aggregates. Photophysical studies also revealed an equilibrium constant of dimerization, K D = 1.5 ± 0.3 M −1, enabling the first thermodynamic quantification of link–link interactions that occur during MOF assembly. Our findings elucidate the role that supramolecular effects play during crystallization of MTV MOFs, opening pathways for the preparation of solid-state materials with solution-like properties by design.